Strength degradation of E-glass plates with circular and square notches - Khechai, Abdelhak; Belarbi, Mohamed Ouejdi; Rekbi, Fares Mohammed Laid (University of Eloued جامعة الوادي, 2018)
In the current investigation, our objective is to determine experimentally the stress concentration in multilayered perforated composite plates subjected to uniaxial tensile loading. The stress concentration factors (SCFs) around circular and square notches are calculated using Digital Image Correlation (DIC) technique. On the other hand, the Finite Element Method (FEM) using FreeFem++ software is employed to validate numerically the experimental findings. The tensile strength degradation of E-glass laminated plates with both circular and square holes is also addressed in the present work through a combination of experimental and numerical studies. The DIC technique is used to obtain full-field surface strain measurements in notched specimens with different hole shapes and sizes, in order to show their effects on SCF and failure strength and failure mechanism.
International Symposium on Mechatronics and Renewable Energies El-Oued 10- 11 December 2018
Keywords: Stress concentration, strength, digital image correlation, composite material, notch